Recovery from bleaching is mediated by threshold densities of background thermo-tolerant symbiont types in a reef-building coral - Bay, Line K. (R Soc Open Sci, 2016)
Sensitive molecular analyses show that most corals host a complement of Symbiodinium genotypes that includes thermo-tolerant types in low abundance. While tolerant symbiont types are hypothesized to facilitate tolerance to temperature and recovery from bleaching, empirical data on their distribution and relative abundance in corals under ambient and stress conditions are still rare. We quantified visual bleaching and mortality of coral hosts, along with relative abundance of C- and D-type Symbiodinium cells in 82 Acropora millepora colonies from three locations on the Great Barrier Reef transplanted to a central inshore site over a 13 month period. Our analyses reveal dynamic change in symbiont associations within colonies and among populations over time. Coral bleaching and declines in C- but not D-type symbionts were observed in transplanted corals. Survival and recovery of 25% of corals from one population was associated with either initial D-dominance or an increase in D-type symbionts that could be predicted by a minimum pre-stress D : C ratio of 0.003. One-third of corals from this population became D dominated at the bleached stage despite no initial detection of this symbiont type, but failed to recover and died in mid to late summer. These results provide a predictive threshold minimum density of background D-type symbionts in A. millepora, above which survival following extreme thermal stress is increased.